My School in the Rain Forest : How Children Attend School Around the World - Ruurs, Margriet (Honesdale, Pa. : Boyds Mills Press, 2009)
At a school that sits on the edge of the Sahara, students are learning to speak English from a teacher who stands in front of a Webcam in North America. These students are learning in a virtual classroom. In another part of the world, kids aren't waiting to ride the bus to school they are waiting to hop in a boat that will take them to a school that floats on a river. And some kids don't mind heights, especially those who attend a school on the slope of a mountain in the Himalayas, in one of the most remote corners of the earth. Margriet Ruurs contacted teachers and volunteers, many of whom took cameras in hand to photograph their schools and students. In this lively photo-essay, readers get to know students from the arid plains of southern Afghanistan to the rain forests of Guatemala who are pursuing their dreams of a brighter future.
New Kids Book 2022 Fall.
Keywords: Schools -- Juvenile literature; Students -- Juvenile literature